A Study of Contract Broiler Production in Lombok, NTB: An Opportunity of Introducing Syariah Partnership - B Indarsih; M H Tamsil; M P Nugroho (Faculty of Animal Science, Bogor Agricultural University, 2010)
A study to evaluate the implementation of integrated poultry production through contract farming system in Lombok, NTB was carried out from June to November 2009. The descriptive methods were used whilst the data was collected using survey methods. Fifty contract farmers were selected to measure the business performance with references on management, performance production index, FCR, and percentage of mortality. The results of this study indicated that the contract broiler production was chosen due to: (1) risk sharing (27.6%), financial credits (25.8%), and the guarantee of marketing (23.3 %). Dissatisfaction particularly in aspects of incentive determination, the quota, and margins. The margin ratios between farmers and integrators, 30%: 70%; 40%: 60% or 50%: 50% with no clear reasons. Performance parameter was as an expectation, suggesting feed quality and management aspects were well implemented. In respect to Syariah bank, its outstanding was well understood but it have not been attractive to the contract farmers. The capital is not the main reason to work with the integrators. The government involvement was needed to encourage poultry industry growth and looking for the new potential region and legislation on maintaining environment. New investors should be encouraged to overcome instability price.